MODIFIKASI MESIN PARUT KELAPA - Erwanto Erwanto; Aditya Wijaya; Diaz Widiantoro Pramono; Miftahul Huda Pamungkas (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Old coconut meat is usually used for household needs. Usually used for making coconut milk for combination ingredients for cooking every day by the community. Demand increases with certain needs and moments, approaching Eid al-Fitr and Eid al-Adha. Based on the results of a field survey to traditional markets located in the Sungailiat area, grated coconut sellers still use coconut grating machines where in the process of grating they still use human hands, even with the help of wood, in 1 hour they can only grate ± 25 coconuts, so the process is finished. slower. At this stage, we conduct a survey and identify problems, determine data needs, data sources will continue with further data collection from observations and research results will be compared to determine product planning to be modified. This design is an illustration before making machine analysis in the form of construction and other components. In designing the machine, it is necessary to know the grating process that will be carried out so that the results used are maximized. In the trial, it was able to grate ± 190 coconuts per hour so that the coconut grater machine looks more optimal in the grating process.